Challenges for nursing in the prevention of cervical cancer (Research, Society and Development, 2023)
Primary health care plays an important role in expanding screening and early detection of cervical cancer (CC), contributing to the reduction of morbidity and mortality. The nurse plays a relevant role as a health educator, where he highlights the importance of performing the Papanicolaou test, however, there are challenges that are faced, such as: the lack of supplies, waiting lists and lack of information about the disease and its consequences. complications. Thus, the objective of the study was to understand the challenges of nursing care in the face of cervical cancer prevention in primary health care. This is a cross-sectional and descriptive study with a qualitative approach, carried out in the city of Bonito - PA. The study included 9 nurses working in the Family Health Strategy who answered a questionnaire via Google Forms with 6 open questions, addressing the difficulties in providing assistance on the prevention of CC. In view of the reports, it was notorious to verify that the marital situation and the low level of knowledge on the subject are among the greatest difficulties, associated with the geographical situation, where some women live far away, consequently not attending the FHS, together with the inadequate environment of the unit and the lack of inputs. It is concluded that, given the factors that interfere with the prevention/early screening of cancer, it is important for nurses to know the reality of their area in order to implement measures that reduce these difficulties and their role as health educators, developing health actions to raise awareness. the female population about CC prevention/screening.